Prevalence of overweight, obesity, and associated factors among healthcare workers in the Gaza Strip, Palestine: A cross-sectional study - Younis, Joma; Jiang, Hong; Fan, Yahui; Wang, Lina; Li, Zhaofang; Jebril, Majed; Ma, Mei; Ma, Le; Ma, Mao; Hui, Zhaozhao (Frontiers in Public Health, 2023)
Background Overweight and obesity are multifactorial conditions that are prevalent in developing and developed countries. They are emerging as a significant public health concern among healthcare workers (HCWs). We aimed to estimate the prevalence of overweight and obesity and their associated factors among HCWs in the Gaza Strip. Methods A cross-sectional study was conducted to recruit 1,850 HCWs aged 22 years and older. Interviews were carried out to collect sociodemographic information, nutritional information, and physical activity. Anthropometric measurements [height, weight, and waist circumference] were conducted with the HCWs. The body mass index was computed to determine the prevalence of overweight and obesity. Chi-square, t-test, and one-way ANOVA were used to compare the variables, and logistic regression was used to examine the associated factors of overweight and obesity. Results The combined prevalence of overweight and obesity among HCWs was 65%. The result of logistic regression showed the risk of being overweight and obesity increased within the age group of 40–49 years (OR = 3.20; 95% CI: 2.37–4.32; P < 0.001). Male participants had more risk of obesity than female participants (OR = 1.77; 95% CI: 1.45–2.15). Married participants had a significantly higher risk of being overweight and obese (OR = 2.52; 95% CI: 2.05–3.28; P = 0.001). Increased monthly income was significantly associated with the risk of being overweight and obese (OR = 2.16; 95% CI: 1.22–3.83; P = 0.008). In addition, hypertension (OR = 2.49; 95% CI: 1.65–3.78; P < 0.001) and type 2 diabetes (OR = 2.42; 95% CI: 1.21–4.85; P= 0.012) were associated with overweight and obesity. Finally, a family history of NCDs was associated with overweight and obesity (OR = 1.69; 95% CI: 1.38–2.07; P < 0.001). Conclusion This study showed a high prevalence of overweight and obesity among HCWs. Age, monthly income, marital status, known hypertension, type 2 diabetes, and eating habits were associated with the prevalence of overweight and obesity compared to other variables that were not associated with overweight and obesity such as profession, vegetables, fruit consumption, and physical activity. Urgent action is needed to tackle overweight and obesity among HCWs.